Electrode plate and battery

By setting a thermal conductive layer in the electrode sheet current collector empty foil area of ​​the lithium-ion battery, using high thermal conductivity thermal impedance carbon material and adhesive, the problem of heat derivation of lithium-ion batteries under high temperature or large-scale charging and discharge conditions is solved. Improves battery safety and electrical performance.

CN119153848APending Publication Date: 2024-12-17ZHUHAI COSMX BATTERY CO LTD

Patent Information

Application Number
CN202411352899.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-26
Publication Date
2024-12-17

AI Technical Summary

Technical Problem

Under high temperature or large-scale charging and discharging conditions, internal heat is difficult to effectively deduce, resulting in problems such as reduced circulation retention rate, battery cell airflow and thermal runaway.

Method used

The thermal conductivity layer is set in the current collector empty foil area of ​​the electrode sheet, and the oxidized thermal impedance carbon material is used to form a thermal conductivity and high resistivity thermal conductivity layer to ensure that heat is exported in time, and through adhesives and aluminum-plastic films Close contact and increase the contact area.

Benefits of technology

It effectively reduces the accumulation of heat inside the battery, improves safety and electrical performance, avoids gas production problems caused by catalytic electrolyte, and improves the long-cycle performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119153848A_ABST
    Figure CN119153848A_ABST
Patent Text Reader

Abstract

The invention provides an electrode plate and a battery comprising the same. The electrode plate comprises an electrode current collector; the active material layer comprises a first active material layer located on the first surface of the current collector; the heat conduction layer comprises a first heat conduction layer located in a first empty foil area of the current collector, and the first empty foil area is an area, where the first active material layer is not arranged, of the first surface of the current collector; the first heat conduction layer comprises a heat conduction impedance carbon material, the heat conductivity coefficient of the first heat conduction layer is larger than or equal to 3 W / (mK), and the powder resistivity of the first heat conduction layer is larger than or equal to 0.2 omega cm. The heat conduction layer is arranged in the empty foil area, without the active material layer, of the current collector, the heat conduction layer comprises the heat conduction impedance carbon material, heat generated by the battery under the high-temperature working condition or the high-rate charging and discharging condition can be conducted out in time, the problem of gas generation caused by catalysis of electrolyte is avoided, and the service life of the battery is prolonged. Therefore, the safety performance and the electrical performance of the battery are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of battery application, and in particular to an electrode plate and a battery. Background Art

[0002] At present, lithium-ion batteries are widely used in various industries due to their advantages such as high energy density, good rate performance and long cycle times. During use, lithium batteries may face high-rate charge and discharge, overcharge, thermal abuse, mechanical abuse and other situations. The battery cell will generate a lot of heat. If the heat cannot be discharged from the battery cell in time, it will accelerate the release of oxygen from the positive electrode active material and the reaction with the electrolyte, as well as the reaction between the negative electrode material and the electrolyte, which may lead to the reduction of cycle retention rate, battery cell inflation, battery cell thermal runaway and other consequences.

[0003] In response to the heat generation of batteries, the industry generally adopts methods such as optimizing the layout of the pole ears, using thicker current collectors, adjusting the amount of conductive agent in the formula, etc. to reduce the heat generation of ohmic heat or polarization heat. However, for heat dissipation, passive heat dissipation is generally relied on, and there is no close contact between the core and the aluminum-plastic film. There is a tiny gap and the electrolyte liquid film is filled inside, which makes the heat dissipation efficiency of the battery low and needs to be improved. Summary of the invention

[0004] In view of this, the present invention provides an electrode plate and a battery. When the electrode plate provided in the present application is used in a battery, it can quickly remove the heat generated inside the battery cell under high temperature conditions or high-rate charge and discharge conditions, reduce the heat accumulation inside the battery, and thus improve the safety and electrical performance of the lithium-ion battery.

[0005] The present application provides an electrode plate, comprising:

[0006] Electrode current collector;

[0007] An active material layer, the active material layer comprising a first active material layer located on a first surface of the current collector;

[0008] A heat-conducting layer, the heat-conducting layer comprising a first heat-conducting layer located in a first empty foil region of the current collector, wherein the first empty foil region is a region on the first surface of the current collector where the first active material layer is not disposed;

[0009] The first heat-conducting layer comprises a thermally conductive resistive carbon material;

[0010] The thermal conductivity of the thermally conductive impedance carbon material is ≥3W / (m•K);

[0011] The powder resistivity of the thermally conductive impedance carbon material is ≥0.2Ω•cm.

[0012] In some specific implementations, the active material layer further includes a second active material layer located on the second surface of the current collector;

[0013] The heat-conducting layer comprises a second heat-conducting layer located in a second hollow foil region of the current collector, wherein the second hollow foil region is a region on the second surface of the current collector where no second active material layer is disposed;

[0014] The second heat-conducting layer comprises a thermally conductive impedance carbon material;

[0015] The thermal conductivity of the thermally conductive impedance carbon material is ≥3W / (m•K);

[0016] The powder resistivity of the thermally conductive impedance carbon material is ≥ 0.2Ω•cm.

[0017] In some specific implementations, the first heat-conducting layer occupies 30% to 100% of the area of ​​the first empty foil region;

[0018] The second heat-conducting layer occupies 30% to 100% of the area of ​​the second hollow foil region.

[0019] In some specific implementations, the first empty foil region is located at the tail of the first current collector;

[0020] The second empty foil region is located at the tail of the second current collector.

[0021] In some specific implementations, the D50 value of the thermally conductive impedance carbon material is 10nm~500nm.

[0022] In some specific implementations, the specific surface area of ​​the thermally conductive carbon material is 10 m 2 / g ~400m 2 / g.

[0023] In some specific implementations, the oil absorption value of the thermally conductive impedance carbon material is ≥30 mL / 100 g.

[0024] In some specific implementations, the thermally conductive impedance carbon material is selected from one or more of oxidized carbon black, graphite or carbon nanotubes.

[0025] In some specific implementations, the first heat-conducting layer further includes an adhesive;

[0026] The second heat conductive layer further includes an adhesive.

[0027] In some specific implementations, the first heat-conducting layer and the second heat-conducting layer independently include 30 wt % to 97 wt % of the thermally conductive impedance carbon material and 3 wt % to 70 wt % of the adhesive.

[0028] In some specific implementations, the adhesive is selected from one or more of polyacrylate, lithium polyacrylate, polyacrylic acid, polyvinyl alcohol, polyimide, polyether ketone, polyether sulfide, polytetrafluoroethylene, polyvinylidene fluoride, polymethyl methacrylate, sodium carboxymethyl cellulose, styrene-butadiene rubber, polystyrene, polyurethane and polyethylene terephthalate.

[0029] In some specific implementations, the room temperature thermal conductivity of the first heat-conducting layer and the second heat-conducting layer are independently ≥ 2W / (m·K);

[0030] The resistivity of the first heat conducting layer and the second heat conducting layer are independently ≥ 2Ω•cm.

[0031] In some specific implementations, the surface density of the first heat-conducting layer and the second heat-conducting layer is independently 0.05 mg / cm 2 ~5mg / cm 2 .

[0032] In some specific implementations, the thickness of the first heat-conducting layer and the second heat-conducting layer are independently 0.2 μm to 30 μm.

[0033] The present application also provides a battery, comprising the electrode plate described in the above technical solution.

[0034] In some specific implementations, the battery includes a packaging shell and a wound battery cell, and the wound battery cell is formed by winding and stacking the electrode sheet, the separator and the second electrode sheet described in the above technical solution.

[0035] In some specific implementations, the thermally conductive layer is located outside the wound battery core.

[0036] The present application sets a heat-conducting layer in the empty foil area of ​​the current collector where no active material layer is set. The heat-conducting layer includes a heat-conducting impedance carbon material, which can not only timely conduct the heat generated by the battery under high temperature conditions or high-rate charge and discharge conditions, but also prevent the problem of gas production caused by catalytic electrolyte, thereby improving the safety and electrical performance of the battery. Furthermore, the heat-conducting impedance carbon material has a high specific surface area and can absorb more electrolyte, which helps to increase the battery's liquid retention and improve the battery's long cycle performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 A schematic diagram of the structure of an electrode plate with a heat conductive layer coated on one side provided in an embodiment of the present application;

[0038] Figure 2 A schematic diagram of the structure of an electrode plate with a heat conductive layer coated on both sides provided in an embodiment of the present application;

[0039] Figure 3A schematic diagram of the structure of a wound battery cell provided in an embodiment of the present application.

[0040] Description of reference numerals:

[0041] 10-electrode current collector;

[0042] 20-active material layer;

[0043] 21- first active material layer;

[0044] 22- second active material layer;

[0045] 30- heat conducting layer;

[0046] 31- first heat conducting layer;

[0047] 32- second heat conducting layer;

[0048] 1- diaphragm;

[0049] 2- positive electrode;

[0050] 201-heat conducting layer

[0051] 3-Negative electrode. DETAILED DESCRIPTION

[0052] It should be understood that the expression "one or more of..." includes each of the items recited after the expression individually and in various different combinations of two or more of the recited items, unless otherwise understood from the context and usage. The expression "and / or" in combination with three or more recited items should be understood to have the same meaning, unless otherwise understood from the context.

[0053] The use of the terms "comprising", "having" or "containing", including their grammatical synonyms, should generally be understood as open and non-restrictive, for example not excluding other unrecited elements or steps, unless otherwise specifically stated or otherwise understood from the context.

[0054] It should be understood that the order of steps or the order in which certain actions are performed is not important as long as the present invention remains operable. In addition, two or more steps or actions may be performed simultaneously.

[0055] The use of any and all examples or exemplary language, such as "for example" or "including", herein is intended only to better illustrate the invention and does not limit the scope of the invention unless otherwise claimed. No language in this specification should be construed as indicating that any non-claimed element is essential to the practice of the invention.

[0056] In addition, the numerical ranges and parameters used to define the present invention are approximate values, and the relevant values ​​in the specific embodiments have been presented as accurately as possible. However, any numerical value inherently inevitably contains standard deviations due to individual test methods. Therefore, unless otherwise expressly stated, it should be understood that all ranges, quantities, values ​​and percentages used in this disclosure are modified by "about". Here, "about" generally means that the actual value is within plus or minus 10%, 5%, 1% or 0.5% of a specific value or range.

[0057] Conventional battery cell structures generally fix the current collector exposed outside the battery cell to the packaging shell, such as aluminum-plastic film, through double-sided tape. Since the current collector and the packaging shell are in surface contact, the contact area is small, and there is isolation from the electrolyte, tape, etc., the thermal conductivity is poor, and the heat generated by the battery cell cannot be discharged in time, which leads to heat accumulation in the battery cell and accelerates the decay of the battery cycle performance.

[0058] In order to improve the puncture resistance and drop resistance, some existing technologies disclose that a ceramic covering layer mainly composed of ceramics and adhesives is set in the empty foil area of ​​the current collector (i.e., the area where the active material layer is not set). However, the ceramic covering layer has poor thermal conductivity. Although it can improve mechanical abuse such as puncture and drop, it will aggravate the deterioration of the cycle performance and safety performance of the battery under high temperature conditions.

[0059] The inventors have found that although setting a thermal conductive material in the empty foil area of ​​the current collector can conduct heat away, most thermal conductive materials commonly used in the battery field, such as carbon black, metal powder, etc., have high electrical conductivity and high specific surface area, strong reaction activity, and can provide many reaction interfaces and directly face the electrolyte. The thermal conductive material will cause the battery to react with the electrolyte at high temperature and high voltage, resulting in gas production, causing the battery cell to swell, which will affect the cycle performance of the battery cell.

[0060] Based on this, the inventors adopt methods such as surface oxidation or coating of carbon materials to introduce oxygen-containing functional groups, such as hydroxyl and carbonyl groups, on the surface of carbon materials, which can greatly reduce the electrical conductivity of carbon materials while having good thermal conductivity, thereby obtaining a material with high thermal conductivity and high impedance. When the high thermal conductivity and high impedance material is arranged in the empty foil area of ​​the current collector to form a thermal conductive layer, since the thermal conductive layer is arranged between the outermost current collector and the aluminum-plastic film, and is in close contact with the two, it can not only timely conduct away the heat generated by the battery under high temperature conditions or high-rate charge and discharge conditions, but also avoid the problem of gas production caused by catalytic electrolyte, thereby improving the safety and electrical performance of the battery.

[0061] See also Figure 1 , Figure 1A schematic diagram of the structure of an electrode pole piece with a single-sided thermal conductive layer provided in an embodiment of the present application, wherein 10 is an electrode current collector, 20 is an active material layer, 21 is a first active material layer, 22 is a second active material layer, 30 is a thermal conductive layer, and 31 is a first thermal conductive layer.

[0062] The electrode plate provided in the embodiment of the present application includes: an electrode current collector 10; an active material layer 20 located on the surface of the current collector; a thermal conductive layer 30, wherein the thermal conductive layer 30 is located in the empty foil area of ​​the current collector 10, and the empty foil area is an area on the surface of the current collector where no active material layer is provided.

[0063] Specifically, the electrode plate provided in the present application can be coated with an active material layer and a heat conductive layer on one side, see Figure 1 In this case, the electrode plate includes an electrode current collector 10, a first active material layer 21 located on the first surface of the current collector 10, a second active material layer 22 located on the second surface of the current collector 10, and a first thermal conductive layer 31 located in the first empty foil area of ​​the current collector 10. The electrode plate provided in the present application can also be coated with active material layers and thermal conductive layers on both sides, see Figure 2 , Figure 2 A schematic diagram of the structure of an electrode plate with a double-sided thermally conductive layer provided in an embodiment of the present application, wherein the electrode plate includes an electrode current collector 10, a first active material layer 21 located on the first surface of the current collector 10, a first thermally conductive layer 31 located in the first empty foil region of the current collector 10, a second active material layer 22 located on the second surface of the current collector 10, and a second thermally conductive layer 32 located in the second empty foil region of the current collector 10. The first surface and the second surface of the current collector 10 are arranged opposite to each other. The first active material layer and the second active material layer are no longer distinguished below, and are collectively referred to as active material layers, the first thermally conductive layer and the second thermally conductive layer are no longer distinguished, and are collectively referred to as thermally conductive layers, and the first empty foil region and the second empty foil region are no longer distinguished, and are collectively referred to as empty foil regions.

[0064] In some specific implementations, there may be a gap between the heat conductive layer and the active material layer located on the same surface of the current collector 10, such as Figure 1 or Figure 2 Those skilled in the art will appreciate that, due to the manufacturing process, the thermal conductive layer and the active material layer on the same surface of the current collector 10 cannot be completely tightly connected when they are connected to each other or close together.

[0065] In some specific implementations, when the active material layer and the thermal conductive layer are coated on both sides of the electrode plate, the active material layer and the thermal conductive layer on both sides may be the same or different, and the present application has no special restrictions on this.

[0066] In some specific implementations, the electrode plate can be a positive electrode plate or a negative electrode plate, and correspondingly, the active material layer is a positive electrode active material layer or a negative electrode material layer. Since the outermost side of a soft-pack lithium-ion battery is generally a positive electrode plate, in a preferred implementation, the electrode plate is a positive electrode plate, and correspondingly, the active material layer is a positive electrode active material layer.

[0067] The electrode plate provided in the embodiment of the present application includes an electrode current collector, which may be a metal foil, including but not limited to aluminum foil, nickel foil, stainless steel or a metal / non-metal composite current collector, etc. For example, when it is a positive electrode plate, the electrode current collector may be aluminum foil, and when it is a negative electrode plate, the electrode current collector may be copper foil.

[0068] An active material layer is arranged on the surface of the electrode current collector. It can be understood that the active material layer is only arranged in a partial area of ​​the surface of the electrode current collector, so that there is an area on the same surface of the electrode current collector where the active material layer is not arranged, which is called the empty foil area.

[0069] In some specific implementations, the active material layer is a positive electrode active material layer, which includes a positive electrode active material, an optional conductive agent and an optional adhesive. In some specific implementations, the mass ratio of the positive electrode active material, the conductive agent and the adhesive is 85~99:0.5~8:0.5~8, preferably 90~99:0.5~5:0.5~5. In some specific implementations, the positive electrode active material includes but is not limited to lithium cobaltate, lithium nickelate, lithium nickel cobalt manganeseate, lithium manganate, lithium nickel manganeseate, lithium nickel cobalt aluminum acid, lithium iron sulfate, lithium iron manganese phosphate, lithium-rich manganese, etc., which can be one or more of them. When the positive electrode active material is a mixture of multiple specific compounds, this application does not make too many restrictions on the ratio between each specific compound. The conductive agent includes but is not limited to carbon black, hard carbon, graphite, carbon nanotubes, graphene, silver powder, nickel powder, tin oxide, conductive titanium dioxide, etc., which can be one or more of them. When the conductive agent is a mixture of multiple specific substances, this application does not make too many restrictions on the ratio between each specific substance. The adhesive includes, but is not limited to, polyvinylidene fluoride, polytetrafluoroethylene, polyacrylic acid, polyamide, lithium polyacrylate, methacrylate, sodium polymethylcellulose, aluminum dihydrogen phosphate, etc., and can be one or more of them. When the adhesive is a mixture of multiple specific substances, this application does not place too many restrictions on the ratio between the specific substances. In some specific implementations, the thickness of the electrode plate is 80μm~130μm, preferably 90μm~120μm. It can be understood by those skilled in the art that the thickness of the electrode plate is actually the thickness of the electrode current collector and the active material layer after rolling, wherein the active material layer can be coated on one side or on both sides.

[0070] In some specific implementations, the heat-conducting layer is disposed in the empty foil region of the electrode current collector, and includes a heat-conducting resistive carbon material, so that the heat-conducting layer has high thermal conductivity and high resistivity.

[0071] In some specific implementations, the thermally conductive impedance carbon material is an oxidized carbon material, and functional groups such as hydroxyl, carbonyl or carboxyl are introduced on the surface of the carbon material to reduce the conductivity of the carbon material. In some specific implementations, the carbon material includes but is not limited to carbon black, hard carbon, artificial graphite, natural graphite, carbon quantum dots, carbon fibers, carbon nanotubes, carbon nanowires, etc., and can be one or more of them. When the carbon material is a composition of multiple specific substances, the application does not limit the amount of each specific substance.

[0072] In some specific implementations, the thermal conductivity of the thermal impedance carbon material is ≥3W / (m•K), preferably ≥20W / (m•K), more preferably ≥30 W / (m•K), and most preferably 30 W / (m•K)~150 W / (m•K). The higher the thermal conductivity of the thermal impedance carbon material, the more conducive it is to the extraction of heat from the inside of the battery cell. However, when the thermal conductivity of the carbon material is improved, its powder resistivity will gradually decrease, which will affect the acupuncture safety performance of the battery cell. In some specific implementations, the thermal conductivity of the thermal impedance carbon material is the thermal conductivity obtained by testing with a transient plane heat source method thermal conductivity tester, and the test steps are as follows: a certain amount of the powder to be tested is spread on the surface of the test dish, and the thermal conductivity of the powder is obtained by instantaneously heating the center of the material and using a thermal resistance sensor to measure the temperature correspondence at different positions.

[0073] The powder resistivity of the thermally conductive impedance carbon material is ≥0.2Ω•cm, preferably 0.2Ω•cm~1000Ω•cm. In fact, the thermal conductivity of the thermally conductive impedance carbon material also affects its powder resistivity. Therefore, in the present application, the thermally conductive impedance carbon material preferably meets the requirements of thermal conductivity, and the powder resistivity is not less than 0.2Ω•cm. Below this value, the decomposition of the catalytic electrolyte will be accelerated at high temperature or high voltage. When it is ≥0.2Ω•cm, the risk of decomposition of the catalytic electrolyte can be greatly reduced, and when the temperature and voltage are further increased, the risk of decomposition of the catalytic electrolyte is also low. At the same time, due to the intrinsic high conductivity of the carbon material, if a very high powder resistance is achieved, a thicker coating layer needs to be used, which increases the cost and affects the thermal conductivity. Therefore, the powder resistivity is preferably ≤1000Ω•cm. In some specific implementations, the powder resistivity is a value measured by a probe method.

[0074] In some specific implementations, the median particle size (D50 value) of the thermal impedance carbon material is 10nm~500nm, preferably 15nm~490nm. Too large a particle size will affect the distribution of the thermal conductive layer coating and may cause relatively large energy losses; too small a particle size will reduce the thermal conductivity of the material. Experimental results show that when the D50 value is 10nm~500nm, it can maintain good thermal conductivity without causing large energy losses, and can have a large specific surface area, which is beneficial to improving the battery's liquid retention level. In some specific implementations, the D50 value is a value obtained by measuring with a Malvern laser particle size analyzer. The specific method is as follows: before testing, 0.5g of the sample is diluted in 50mL of 25% ethanol solution and ultrasonicated for 2min, and then the ultrasonicated liquid is pumped into the laser particle size analyzer, and the shading degree is controlled to be 15%. The median particle size D50 value of the measured sample is obtained by testing.

[0075] In some specific implementations, the specific surface area of ​​the thermally conductive carbon material is 10 m 2 / g ~400m 2 / g, preferably 15m 2 / g ~300m 2 / g, more preferably 50m 2 / g ~150m 2 / g. The larger the specific surface area of ​​the thermal impedance carbon material, the stronger its liquid storage capacity and the more liquid it retains. When the battery electrolyte is consumed, it can be released into the electrode to improve the long cycle performance of the battery. However, too large a specific surface area will also increase water absorption and other problems, and it is necessary to increase the time of the battery cell baking and dehydration process. The experimental results show that the specific surface area of ​​the thermal impedance carbon material is 10m 2 / g ~400m 2 / g, the liquid retention of the prepared battery can reach an optimal level, and there is no need to increase the preparation time. In some specific implementations, the specific surface area of ​​the thermal impedance carbon material is a specific surface area measured by a BELSORP MINI X specific surface area analyzer using a gas adsorption and desorption method.

[0076] In some specific implementations, the oil absorption value of the thermally conductive impedance carbon material is ≥30mL / 100g, preferably ≥90mL / 100g, and more preferably 100mL / 100g~230 mL / 100g. The oil absorption value directly reflects the adsorption capacity of the material for the electrolyte. The higher the oil absorption value, the more helpful it is to improve the liquid retention. However, the oil absorption value depends on the lipophilicity and specific surface area of ​​the carbon material surface. There is a limit value, which should generally be ≤230 mL / 100g. In some specific implementations, the oil absorption value is the value obtained by testing using the manual test method in the national standard GB / T 3780.2-2003 "Determination of the absorption value of dibutyl phthalate in the second part of carbon black", specifically: put a sufficient amount of carbon black sample into a suitable container, dry it in an oven, take it out and place it in a dryer, and cool it to room temperature. Accurately weigh the dried carbon black sample and put it in an appropriate container. Place the sample on a glass plate (if it is granular carbon black, it must be crushed first), add oil to the sample at a rate of 2 to 4 drops per second, and stir continuously during the dropping process. When the amount of oil added reaches two-thirds of the standard carbon black oil absorption value, use a glass rod to fully mix the oil and carbon black to make it evenly infiltrated. Then, continue to add oil at a slower speed, stirring and rolling at the same time, until thin strips or small pieces of agglomerates appear, then stop dropping oil. Subsequently, calculate the oil absorption value of carbon black and clean the mixing tank.

[0077] In some specific implementations, the heat-conducting layer also includes an adhesive, which can form direct contact between the heat-conducting layer and the packaging shell such as aluminum-plastic film when encapsulated, thereby expanding the contact area and facilitating the timely extraction of heat. The adhesive includes, but is not limited to, polyacrylate, lithium polyacrylate, polyacrylic acid, polyvinyl alcohol, polyimide, polyether ketone, polyether sulfide, polytetrafluoroethylene, polyvinylidene fluoride, polymethyl methacrylate, sodium carboxymethyl cellulose, styrene-butadiene rubber, polystyrene, polyurethane and polyethylene terephthalate, etc., which are commonly used adhesives in the lithium battery industry and can be one or more of them. When the adhesive is a mixture of multiple specific substances, the application does not limit the amount of each specific substance.

[0078] In some specific implementations, the thermal conductive layer includes 30 wt% to 97 wt% of thermal conductive resistance carbon material and 3 wt% to 70 wt% of adhesive, preferably 40 wt% to 95 wt% of thermal conductive resistance carbon material and 5 wt% to 60 wt% of adhesive.

[0079] In some specific implementations, the room temperature thermal conductivity of the thermally conductive layer is ≥2W / (m·K), preferably ≥10W / (m·K), and more preferably 20W / (m·K)~130W / (m·K). The greater the thermal conductivity of the thermally conductive layer, the more conducive it is for the heat inside the battery to be transferred to the surface of the battery body with the help of the thermally conductive layer, thereby reducing the heat accumulation inside the battery. At the same time, since the thermally conductive layer is mainly limited by the thermal conductivity of the filler itself, the thermal conductivity of the thermally conductive layer in this application is preferably ≤130W / (m·K). In some specific implementations, the thermal conductivity of the thermally conductive layer is a value obtained by testing using a flat plate heat flow meter thermal conductivity tester. The specific steps are as follows: by adding a stable hot surface temperature to one side of the sample, heat is transferred through the sample to the cold surface (room temperature), and the transferred heat flow is measured to calculate the thermal conductivity.

[0080] At the same time, the resistivity of the thermal conductive layer is ≥2Ω•cm, preferably ≥10Ω•cm, and more preferably 15Ω•cm~10000Ω•cm. When the powder resistivity of the thermally conductive impedance carbon material is large, the resistivity of the obtained thermally conductive layer is generally also high. When the resistivity is ≥2Ω•cm, it can isolate the current collector, such as aluminum foil, and form a passivation cover on the current collector, which has a certain improvement effect in tests such as needle puncture. Since the resistivity of the coating is limited by the powder resistivity size and addition amount of the thermally conductive impedance carbon material and the thickness of the coating, there will be a maximum value of the limit. In this application, the resistivity of the thermal conductive layer is preferably ≤10000Ω•cm. In some specific implementations, the resistivity of the thermal conductive layer is the value obtained by testing with a lattice ST2258C pole piece resistivity tester, which is specifically as follows: place a pole piece of a certain area under a four-probe probe, look up the table to input the correction coefficient 𝒑 corresponding to the pole piece coating thickness into the tester, and then test it. After the reading is stable, record the resistivity and test 5 positions to take the average value.

[0081] In some specific implementations, the surface density of the thermal conductive layer is 0.05 mg / cm 2 ~5mg / cm 2 , preferably 0.1 mg / cm 2 ~1mg / cm 2 If the surface density of the thermal conductive layer is too high, the thermal conductivity will be reduced, while if it is too low, it will increase the difficulty of coating and cause problems such as foil leakage. The surface density of the thermal conductive layer is 0.05 mg / cm 2 ~5mg / cm 2 In some specific implementations, the surface density is a value obtained by testing in the following way: the electrode with coating and the empty foil without coating are placed on an area of ​​1000mm 2A round punch is used to cut out discs of fixed area, and the weight of the electrode including the coating and the weight of the empty foil are weighed respectively. The ratio of the weight difference to the area is the surface density of the coating.

[0082] In some specific implementations, the thickness of the heat conductive layer is 0.2 μm to 30 μm, preferably 1 μm to 20 μm, and more preferably 5 μm to 15 μm. In one embodiment of the present application, the thickness of the heat conductive layer is lower than that of the active material layer, which is conducive to direct contact with the packaging shell.

[0083] In some specific implementations, the empty foil area is located at the tail of the current collector and can be in contact with the packaging shell, such as an aluminum-plastic film, and has a good thermal conductivity. In some specific implementations, the heat-conducting layer occupies 30% to 100% of the area of ​​the empty foil area, preferably 50% to 100%. The heat-conducting layer is arranged in the empty foil area where there is no active material layer on the surface, so that the heat-conducting layer can be directly in contact with the current collector and the packaging shell, such as an aluminum-plastic film, so as to achieve a better thermal conductivity; if the heat-conducting layer is arranged between the current collector and the active material layer, its thermal conductivity will be lost due to the barrier effect of the active material layer.

[0084] The present application has no special restrictions on the preparation method of the electrode sheet, and the electrode sheet can be prepared according to the following method:

[0085] coating an active material on at least one surface of a current collector to form an active material layer;

[0086] The heat-conducting layer material is coated on the empty foil area on the same surface of the current collector, and the heat-conducting layer is formed after baking and rolling to obtain the electrode plate.

[0087] The present application has no special restrictions on the coating method. For example, the coating can be selected from extrusion coating, transfer coating, gravure coating, spray coating, etc. The present application has no special restrictions on the baking and rolling, as long as the thermal conductive layer is adhered and formed.

[0088] The present application also provides a battery, including the electrode sheet described in the above technical solution. In some specific implementations, the battery includes a packaging shell and a wound battery cell, and the wound battery cell is formed by winding the electrode sheet, the separator and the second electrode sheet described in the above solution. Figure 3 , Figure 3 It is a schematic diagram of the structure of the wound battery cell provided in an embodiment of the present application, wherein 1 is a separator, 2 is a positive electrode sheet, 3 is a negative electrode sheet, and 201 is a heat conductive layer.

[0089] The heat-conducting layer 21 is arranged on the outside of the wound battery cell, and can achieve close contact with the packaging shell, such as an aluminum-plastic film, thereby enhancing the heat dissipation capacity of the battery. The heat generated by the side reactions or ohmic heat inside the battery can be timely conducted to the outside of the battery through the heat-conducting layer for heat dissipation, thereby reducing the problems of capacity attenuation and increased internal resistance caused by the inability to dissipate the heat in time; at the same time, since the heat-conducting layer has low conductivity and is arranged in the empty foil area, when it directly contacts the electrolyte, the gas production problem caused by the catalytic electrolyte will not occur, and it can bring safety performance, such as needle puncture, falling and other performance improvements. At the same time, since the thermal impedance carbon material forming the heat-conducting layer has a relatively high specific surface area, it can absorb more electrolyte, so that the electrolyte can be slowly released to be replenished during the gradual consumption of the electrolyte inside the battery cell, thereby improving the cycle performance of the battery.

[0090] In some specific implementations, the battery may be a lithium-ion battery. In this case, the electrode plate described in the above technical solution is a positive electrode plate, and the second electrode plate is a negative electrode plate. The present application does not specifically limit the negative electrode plate. For example, the negative electrode plate includes a negative electrode current collector and a negative electrode active material layer disposed on the surface of the negative electrode current collector, wherein the negative electrode current collector includes but is not limited to one or more of a copper current collector, a nickel current collector, and a stainless steel current collector; the negative electrode active material includes but is not limited to one or more of artificial graphite, natural graphite, hard carbon, soft carbon, lithium titanate, and silicon negative electrode materials. When the negative electrode material is a mixture of multiple specific materials, the present application does not specifically limit the ratio between the specific materials.

[0091] In some specific implementations, the diaphragm includes but is not limited to glass fiber microporous membrane, polyester microporous membrane, polyethylene microporous membrane, polypropylene microporous membrane, polytetrafluoroethylene microporous, ceramic coated diaphragm, etc.

[0092] In some specific implementations, the electrolyte in the lithium-ion battery may include a lithium salt, an organic solvent, and an additive, wherein the lithium salt includes, but is not limited to, one or more of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium difluorooxalate borate, lithium bisoxalate borate, lithium bisfluorosulfonyl imide, lithium bistrifluoromethanesulfonyl imide, lithium difluorophosphate, lithium peraluminate, and lithium hexafluoroarsenate; the organic solvent includes, but is not limited to, one or more of dimethyl carbonate, diethyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, ethylene carbonate, ethyl propionate, ethyl acetate, methyl acetate, dimethyl acetate, methyl butyrate, and n-propyl acetate; the additive includes, but is not limited to, one or more of vinylene carbonate, fluoroethylene carbonate, 1,3-propane sultone, vinyl sulfate, diphenyl carbonate, toluene carbonate, acrylic nitrile, succinic anhydride, succinonitrile, and adiponitrile. When the lithium salt, organic solvent, or additive is a mixture of multiple specific substances, the present application has no special restrictions on the ratio between the specific substances.

[0093] The electrode plate and battery provided in the present application are further described below in conjunction with the embodiments.

[0094] Embodiments 1 to 14

[0095] The active material lithium cobalt oxide, conductive carbon black and adhesive PVDF are added to the solvent NMP in a mass ratio of 98:1:1 for dispersion. After dispersion, they are coated on a partial area of ​​the surface of the positive electrode aluminum foil current collector by a coating machine to form a positive electrode material paste area. The area on the same surface of the positive electrode aluminum foil current collector that is not coated with the positive electrode material is a blank foil area.

[0096] After adding thermally conductive high-impedance carbon black and adhesive PVDF in a mass ratio of 88:12 to N-methylpyrrolidone for dispersion, a coating machine was used to coat the empty foil area at the tail of the positive electrode aluminum foil current collector, accounting for 98% of the area of ​​the empty foil area at the tail. The parameters of thermally conductive high-impedance carbon black are shown in Table 1.

[0097] The positive electrode aluminum foil current collector is baked and rolled to form a positive electrode active material layer and a thermal conductive layer, respectively, to obtain a positive electrode sheet, wherein the thickness of the positive electrode active material layer on a single side is 40 um; the parameters of the thermal conductive layer are shown in Table 2.

[0098] Table 1 Parameters of thermally conductive high impedance carbon black

[0099]

[0100] Table 2 Parameters of thermal conductive layer

[0101]

[0102] Comparative Example 5

[0103] Compared with Example 1, the difference is that there is no heat conductive layer.

[0104] Test example

[0105] Active material artificial graphite and adhesive SBR are added into solvent deionized water at a mass ratio of 98.5:1.5 for dispersion. After dispersion, they are coated on the surface of copper foil using a coating machine. After baking and rolling, the negative electrode sheet is obtained.

[0106] The positive electrode sheet, negative electrode sheet and separator prepared in the above embodiments and comparative examples are wound in order to obtain a winding core, and the winding core is packaged, injected, formed and sorted to obtain a lithium-ion battery. Among them, the separator is composed of a separator substrate and a glue layer, wherein the material of the separator is polypropylene with a thickness of 6um, and the two surfaces of the substrate are each coated with a 1um thick polyvinylidene fluoride adhesive layer, and the electrolyte is composed of a lithium salt and a solvent, wherein the lithium salt is selected from lithium hexafluorophosphate with a concentration of 1mol / L, and the solvent is composed of diethyl carbonate (DEC), dimethyl carbonate (DMC), and ethyl methyl carbonate (EMC), and the volume ratio is 1:1:1.

[0107] The obtained lithium-ion battery was tested according to the following method. The results are shown in Table 3. Table 3 shows the performance parameters of the lithium-ion batteries prepared in the examples and comparative examples of the present application.

[0108] 45℃ cycle test: At 45℃, the battery is subjected to 1C / 1C charge and discharge cycle test. The ratio of capacity to initial capacity after 500T of test cycle is regarded as capacity retention rate, and the change rate of DC impedance after 500T to initial DC impedance is regarded as internal resistance growth rate.

[0109] Performance test of 24H storage at 80℃: The battery is charged to the maximum voltage at 1C constant current and constant voltage with a cut-off current of 0.05C, and placed in a constant temperature box at 80℃. The percentage increase in battery thickness before and after the test is regarded as the battery expansion rate, which is used to characterize the gas production level of the battery.

[0110] Puncture test: Charge the single battery at 1C constant current and constant voltage to the highest voltage, with a cut-off current of 0.05C. Use a 2.0mm diameter steel needle for puncture at a speed of 300mm / s to puncture the battery in the center. Keep for 30 minutes. Test 10 batteries in each group. The battery is considered to have passed if it does not catch fire.

[0111] Determination of liquid retention coefficient: The ratio of the gram weight of the electrolyte in the battery to the capacity of the battery is regarded as the liquid retention coefficient of the battery. The gram weight of the electrolyte is measured by the weight after injection and before packaging, minus the weight of the packaged battery cell and the weight of the airbag bag.

[0112] Table 3 Performance parameters of lithium-ion batteries prepared in the present embodiment and comparative example

[0113]

[0114] It can be seen from Table 3 that, compared with Comparative Example 5 where no thermal conductive layer is set, Comparative Example 1 uses carbon black with low thermal conductivity and high resistivity to set the thermal conductive layer. Although the pass rate of the battery's puncture test is improved, the 45°C internal resistance growth rate and 85°C storage expansion rate of the battery are increased, that is, its impedance growth and high-temperature gas production risks are increased, and the 45°C cycle retention rate is slightly reduced; Comparative Example 2 uses carbon black with high thermal conductivity and low resistivity to set the thermal conductive layer. Although the 45°C internal resistance growth rate of the battery is reduced and the impedance growth rate is reduced, the high-temperature gas production risk of the battery is increased, the 85°C storage expansion rate is increased, and the puncture performance pass rate is not improved, and the 45°C cycle retention rate is Slightly decreased; Comparative Example 3 uses carbon black with high thermal conductivity, high resistivity but too small particle size to set the thermal conductive layer. Although it improves the battery's needle test pass rate, reduces the battery's 45°C internal resistance growth rate, and the impedance growth rate becomes smaller, it significantly increases the battery's 85°C storage expansion rate, increases the risk of high-temperature gas production, and the 45°C cycle retention rate decreases slightly; Comparative Example 4 uses carbon black with high thermal conductivity, high resistivity but too large particle size to set the thermal conductive layer. Although it increases the 45°C cycle retention rate, reduces the battery's 45°C internal resistance growth rate, the impedance growth rate becomes smaller, and reduces the battery's 85°C storage expansion rate, there is no significant improvement in the battery's needle test pass rate. It can be seen that the thermal conductivity, resistivity and particle size of the carbon black that forms the thermal conductive layer will affect the comprehensive performance of the battery.

[0115] The lithium-ion batteries prepared in the examples of the present application can maintain good comprehensive performance, including high 45°C cycle retention rate, low 45°C internal resistance growth rate, low 85°C storage expansion rate, good needle puncture test pass rate and high liquid retention, etc., especially good needle puncture test pass rate. Specifically, among the batteries prepared in Examples 1 to 14 of the present application, the needle puncture test pass rate of most batteries can reach 10 / 10, and the lowest can reach 5 / 10 or more, which is significantly higher than that of batteries without a thermal conductive layer and batteries with a thermal conductive layer formed of low resistivity carbon black;

[0116] Examples 1 to 3 show that within the range of 3 W / (mK) to 150 W / (mK), the higher the thermal conductivity of carbon black, the higher the 45°C cycle retention rate of the battery, the smaller the 45°C internal resistance growth rate, the smaller the impedance growth, the smaller the 85°C storage expansion rate, and the lower the risk of gas generation during high-temperature storage;

[0117] Examples 1, 4 and 5 show that the higher the resistivity of carbon black, the lower the battery expansion rate at 85°C storage and the lower the risk of gas generation at high temperature storage;

[0118] Examples 1, 6 to 8 show that when the particle size of carbon black is above 10 nm, the larger the particle size of carbon black, the higher the 45°C cycle retention rate of the battery, the lower the 45°C internal resistance growth rate, the lower the impedance growth, the smaller the 85°C storage expansion rate, and the lower the risk of gas production during high-temperature storage. However, if the particle size is too large, the pass rate of the puncture test will decrease.

[0119] Examples 1, 9 and 10 show that the lower the coverage area of ​​the thermal conductive layer, the lower the 45°C cycle retention rate of the battery, the greater the 45°C internal resistance growth rate, the greater the impedance growth, and the lower the puncture test pass rate, but the smaller the 85°C storage expansion rate, the lower the risk of gas production during high-temperature storage.

[0120] Examples 1 and 11 to 14 show that as the coating surface density increases, the thermal conductivity of the electrode decreases, the 45°C cycle retention rate of the battery decreases, the 45°C internal resistance growth rate increases, the impedance growth increases, the 85°C storage expansion rate increases, the risk of gas production during high-temperature storage increases, the puncture test pass rate increases, and the liquid retention coefficient and liquid retention amount also increase accordingly.

[0121] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. An electrode plate, comprising: Electrode current collector; An active material layer, the active material layer comprising a first active material layer located on a first surface of the current collector and / or a second active material layer located on a second surface of the current collector; A heat-conducting layer, the heat-conducting layer comprising a first heat-conducting layer located in a first empty foil region of the current collector and / or a second heat-conducting layer in a second empty foil region, the first empty foil region being a region on the first surface of the current collector where no first active material layer is disposed, and the second empty foil region being a region on the second surface of the current collector where no second active material layer is disposed; The first heat-conducting layer and the second heat-conducting layer independently comprise a thermally conductive resistive carbon material; The thermal conductivity of the thermally conductive impedance carbon material is ≥3W / (m•K); The powder resistivity of the thermally conductive impedance carbon material is ≥0.2Ω•cm.

2. The electrode plate according to claim 1, characterized in that: The first heat-conducting layer occupies 30% to 100% of the area of ​​the first empty foil region; and / or The second heat-conducting layer occupies 30% to 100% of the area of ​​the second hollow foil region.

3. The electrode plate according to claim 2, characterized in that: The first empty foil region is located at the tail of the first surface of the current collector; and / or The second empty foil area is located at the tail of the second surface of the current collector.

4. The electrode plate according to any one of claims 1 to 3, characterized in that: The D50 value of the thermal conductivity impedance carbon material is 10nm~500nm.

5. The electrode plate according to claim 4, characterized in that: The thermally conductive carbon material has at least one of the following parameters: The specific surface area of ​​the thermal conductivity carbon material is 10 m 2 / g ~400m 2 / g; The oil absorption value of the thermally conductive impedance carbon material is ≥30 mL / 100 g.

6. The electrode plate according to claim 5, characterized in that: The thermally conductive impedance carbon material is selected from one or more of oxidized carbon black, graphite or carbon nanotubes.

7. The electrode plate according to any one of claims 1 to 3, characterized in that: The first heat-conducting layer and the second heat-conducting layer independently include 30 wt % to 97 wt % of a heat-conducting resistance carbon material and 3 wt % to 70 wt % of an adhesive.

8. The electrode plate according to any one of claims 1 to 3, characterized in that: The first heat conducting layer and the second heat conducting layer independently have at least one of the following parameters: The room temperature thermal conductivity of the first heat-conducting layer and the second heat-conducting layer are independently ≥ 2W / (m·K); The resistivity of the first heat-conducting layer and the second heat-conducting layer are independently ≥ 2Ω•cm; The surface density of the first heat-conducting layer and the second heat-conducting layer is independently 0.05 mg / cm 2 ~5mg / cm 2 ; The thickness of the first heat-conducting layer and the second heat-conducting layer are independently 0.2 μm to 30 μm.

9. A battery comprising the electrode sheet according to any one of claims 1 to 8.

10. The battery according to claim 9, characterized in that The heat-conducting layer is located outside the wound battery core or the laminated battery core.

Citation Information

Patent Citations

  • Positive plate and application thereof

    CN117219727A

  • Positive pole piece, battery and electric device

    CN117542953A

  • Lithium ion battery positive electrode with high specific capacity and long cycle life

    CN117747747A

  • Electrode plate and lithium ion battery

    CN220895544U

  • Battery core

    WO2019104534A1

Cited By

  • Battery cell structure and lithium ion battery

    CN119542614A